Updated Australian consensus statement on management of inherited bleeding disorders in pregnancy. Issue 7 (29th March 2019) - Dunkley, Scott; Curtin, Julie A; Marren, Anthony J; Heavener, Robert P; McRae, Simon; Curnow, Jennifer L
Abstract: Introduction: There have been significant advances in the understanding of the management of inherited bleeding disorders in pregnancy since the last Australian Haemophilia Centre Directors' Organisation (AHCDO) consensus statement was published in 2009. This updated consensus statement provides practical information for clinicians managing pregnant women who have, or carry a gene for, inherited bleeding disorders, and their potentially affected infants. It represents the consensus opinion of all AHCDO members; where evidence was lacking, recommendations have been based on clinical experience and consensus opinion. Main recommendations: During pregnancy and delivery, women with inherited bleeding disorders may be exposed to haemostatic challenges. Women with inherited bleeding disorders, and their potentially affected infants, need specialised care during pregnancy, delivery, and postpartum, and should be managed by a multidisciplinary team that includes at a minimum an obstetrician, anaesthetist, paediatrician or neonatologist, and haematologist. Recommendations on management of pregnancy, labour, delivery, obstetric anaesthesia and postpartum care, including reducing and treating postpartum haemorrhage, are included. The management of infants known to have or be at risk of an inherited bleeding disorder is also covered. Changes in management as a result of this statement: Key changes in this update include the addition of a summary of the expected physiological changes in coagulation factors and phenotypic severity of bleeding disorders in pregnancy; a flow chart for the recommended clinical management during pregnancy and delivery; guidance for the use of regional anaesthetic; and prophylactic treatment recommendations including concomitant tranexamic acid.